Female religious authority in Shiʻi Islam : past and present - Künkler, Mirjam, 1977-; Stewart, Devin J. (Edinburgh : Edinburgh University Press, 2021)
"Islamic religious authority is conventionally understood to be an exclusively male purview. Yet when dissected into its various manifestations--leading prayer, preaching, issuing fatwas, transmitting hadith, judging in court, teaching law, theology, and other Islamic sciences and generally shaping the Islamic scholarly tradition--nuances emerge that hint at the presence of women in the performance of some of these functions. This collection of case studies, covering the period from classical Islam to the present, and taken from across the Shi'i Islamic world, reflects on the roles that women have played in exercising religious authority across time and space. Comparative reflection on the case studies allows for the formulation of hypotheses regarding the conditions and developments--whether theological, jurisprudential, social, economic, or political--that enhanced or stifled the flourishing of female religious authority in Shi'i Islam."--
1. Introduction / Mirjam Künkler and Devin Stewart -- 2. Forgotten histories of female religious authority in Islam / Mirjam Künkler -- 3. Umm Salamah : A female authority legitimating the authorities / Yasmin Amin -- 4. Heiress to the Prophet : Fatima's khutba as an early case of female religious authority in Islam / Alyssa Gabbay -- 5. Female authority in the times of the Shi‘i Imams / Liyakat Takim -- 6. "She should not raise her voice when amongst men" : Imāmī arguments against (and for) women judges / Robert Gleave -- 7. Husniyyah's debate at the court of Harun al-Rashid : Sectarian polemics and female religious authority / Devin Stewart -- 8. Layli as Queen of Heaven by Muhammadi of Herat, c. 1565 / Michael Barry -- 9. Princesses, patronage, and the production of knowledge in Safavid Iran / Yusuf Ünal -- 10. The lives of two mujtahidat : Female religious authority in twentieth-century Iran / Mirjam Künkler and Roja Fazaeli -- 11. The other half of the mission : Amina 'Bint al-Huda' as a representative (Wakila) of Muhammad Baqir al-Sadr / Raffaele Mauriello -- 12. The Alimat of Sayyida Zaynab : Female Shi‘i religious authority in a Syrian seminary / Edith Szanto -- 13. Women's religious seminaries in Iran : A diversified system despite state attempts at unification and standardisation / Maryam Rutner.
Includes bibliographical references and index.
Mirjam Künkler is Senior Research Fellow at Swedish Collegium for Advanced Study. Devin Stewart is Professor of Arabic and Islamic Studies at Emory University.
Print version record.
eBooks on EBSCOhost
Keywords: Shiite women -- Case studies; Women in Islam -- Case studies; Authority -- Religious aspects -- Islam -- Case studies; Shiite women; Women in Islam; Authority -- Religious aspects -- Islam; Femmes chiites; Femmes dans l'islam.; Autorité -- Aspect religieux -- Islam; Femmes chiites -- Études de cas; Femmes dans l'islam -- Études de cas; Autorité -- Aspect religieux -- Islam -- Études de cas; HISTORY / Middle East / General; Authority -- Religious aspects -- Islam; Shiite women; Women in Islam; Electronic books; Case studies; Case studies; Études de cas